2023
DOI: 10.3390/ijerph20031849
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Effects of Plyometric Training on Lower Limb Explosive Strength in Adolescent Athletes

Abstract: Background: Plyometric training is an effective training method to improve explosive strength. However, the ability to perform plyometric training in the adolescent population is still controversial, with insufficient meta-analyses about plyometric training on lower limb explosive strength in adolescent athletes. Objective: To investigate the influence of plyometric training on the explosive strength of lower limbs in adolescent athletes. Methods: We performed a search of six databases (Web of Science, PubMed,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 59 publications
4
15
0
Order By: Relevance
“…In the case of SJ, HGCF seems to yield better results, followed by MGCF and LGCF. Similar to the results of most meta-analyses on the effects of plyometric training on jumping ability 8 , 9 , 25 , 26 , this study also found that plyometric training is an effective method for improving jumping performance in adolescents. Mark et al 27 conducted a similar experimental study to this one, where they divided all participants into low, moderate, and high-intensity training groups based on the different ground contact frequencies per week.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…In the case of SJ, HGCF seems to yield better results, followed by MGCF and LGCF. Similar to the results of most meta-analyses on the effects of plyometric training on jumping ability 8 , 9 , 25 , 26 , this study also found that plyometric training is an effective method for improving jumping performance in adolescents. Mark et al 27 conducted a similar experimental study to this one, where they divided all participants into low, moderate, and high-intensity training groups based on the different ground contact frequencies per week.…”
Section: Discussionsupporting
confidence: 86%
“…The results of the meta-analysis indicate that plyometric training is an effective method for improving jumping performance, which supports the view that plyometric training can improve lower limb explosiveness 8 , 24 , 25 . Subgroup analyses indicate that different TGCTs induce specific adaptations in each type of jump.…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations